Germany Above All: Nationalism as a Tool for German Imperialism - 1890-1914 - Pimenta Starling, Bruno (Temporalidades, 2022)
Abstract: The objective of this paper is to show how Germany, between 1890 and 1914, used nationalism as a way to make its foreign policy viable. The effort to identify the State’s interests as the interests of the nation was carried out in order to raise social, political and economic resources for the execution of the Weltpolitik. This was a top down idea, imposed from State to society, in such a way that there was a sense of unity and national cohesion between the German population and the government. We rely on the concepts of nation and nationalism as proposed by Benedict Anderson and Eric J. Hobsbawm, as well as on the International Relations neoclassical realist theory, which provide us with the necessary instruments for our research. As sources, we look into political speeches, testimonies and official documents of the period, such as the Constitution of the German Empire. Keywords: Germany, nationalism, imperialism.